Inserting Message Secret on File Data Bank using Steganography Engineering with EoF (End of File) Method - Michael Sitorus; Deki Satria (Kresnamedia Publisher, 2020)
Exchanging information does not realize that is important information. Circulates often important information insignificant but such as account bank customer information. The threat of security to information such as interruption, interception, modification, and fabrication. Thefts of information data by irresponsible parties. This research aims to secure information data in the form file digital image to be inserted with a secret message on building application for a secret message security system in the Bank with applying steganography using the End Of File (EOF) method. Steganography application capable of inserting secret messages in digital image data files. The results of the research can keep the existence of the message hidden. When other people receive image files, they can only see the images with the naked eye. So all messages are invisible and will not be read for hackers or other people before knowing the security side and open of password or reading the secret message.